Hot Glue Gun Releasing Biocompatible Tissue Adhesive. (28th March 2019) - Shagan, Alona; Zhang, Wei; Mehta, Manisha; Levi, Shira; Kohane, Daniel S.; Mizrahi, Boaz
Abstract: Tissue bioadhesives are widely used in dermatology, surgery rooms, and in the field. Despite their advantages over sutures and staples, currently available tissue glues are limited by their mechanical properties and toxicity. Here, a new approach is described for wound closure that is based on a biocompatible, low melting point four‐armed N ‐hydroxy succinimide‐modified polycaprolactone (star‐PCL‐NHS). Star‐PCL‐NHS is inserted into a hot melt glue gun, melts upon minimal pressure, and is extruded directly onto the wound, where it solidifies, bonding strongly with both edges of the wound. Changes in molecular weight allow control of adhesive strength, melting point, and elasticity properties. In vitro and in vivo evaluations confirm the biocompatibility of this system. The straightforward synthetic scheme and the simple delivery method, combined with the desirable mechanical properties, tunability, and tissue compatibility, are desirable traits in wound management. Abstract : A hot‐melt glue gun for tissue bioadhesion, where the glue is a biocompatible polymer with low melting temperature. This system offers a clinically safe and convenient way of applying tissue adhesives and opens new routes for administration of biocompatible formulations.